Analysis of Dichotomous Questions with IRT for Diagnostic Tests in Statistics Courses - Andhita Dessy Wulansari (Indonesian Mathematics Education Journal, 2024)
The results of the question item analysis can be used as diagnostic information, whether students understand the concepts, have misconceptions, and need help understanding the concepts of the lecture's material. The diagnostic test here consists of 20 multiple-choice questions to identify the level of conceptual understanding of the primary statistics material in the introductory statistics course. In this study, researchers will conduct item analysis using Item Response Theory (IRT). This research aims to determine the questions' quality and the abilities of FTIK IAIN Ponorogo students. This research is evaluative research with a quantitative descriptive approach. The research results show that in terms of model suitability, based on the AIC, BIC, and log-likelihood criteria, itfor this case, the 1PL model is the most suitable compared to the 2PL and 3PL models. Based on the ICC 1PL curve, it can be seen that item number 9 is the most accessible item, and item number 4 is the most challenging item. to the right, the difficulty level of the question item is lower, and further to the left, the difficulty level of the question is higher. The estimated value of the person's ability (person) for each participant totaling 1000 people is symbolized by p1 to p1000. The test taker's ability (ϴ) varies from -3.45106849 to 3.38603802.